Characterization of wastewater in the carton packaging industry: Case: Cartones Villa Marina - Meza-Mansilla, Flavia (2021)
The aim of this research was to characterize the parameters of the effluent generated in the cleaning process of printing machines, corrugators, rubber preparation reactors as an input for the manufacture of corrugated cardboard packaging, and compare them with the values after the processes coagulation-flocculation in a first stage, the following treatments were electroflotation (EF), electrocoagulation (EC) and gravel and sand filtration beds; For the characterization, the CERPER laboratory carried out the sampling of the waters, measuring in situ the parameters of pH, conductivity and temperature; SST, TDS, COD, BOD, Oils and Fats and Total Metals were measured in the laboratory. The results of the untreated water, the wastewater treated with gravel and sand filters, and the treated wastewater from reverse osmosis are shown in Table 4.